Thermal decomposition of binary mixtures of organic activators used in no-clean fluxes and impact on PCBA corrosion reliability. Issue 2 (19th August 2019) - Piotrowska, Kamila; Li, Feng; Ambat, Rajan
Abstract : Purpose: The purpose of this paper is to investigate the decomposition behavior of binary mixtures of organic activators commonly used in the no-clean wave flux systems upon their exposure to thermal treatments simulating wave soldering temperatures. The binary blends of activators were studied at varying ratios between the components. Design/methodology/approach: Differential scanning calorimetry and thermogravimetric analysis were used to study the characteristics of weak organic acid (WOA) mixtures degradation as a function of temperature. The amount of residue left on the surface after the heat treatments was estimated by gravimetric measurements as a function of binary mixture type, temperature and exposure time. Ion chromatography analysis was used for understanding the relative difference between decomposition of activators in binary blends. The aggressivity of the left residue was assessed using the acidity indication gel test, and effect on reliability was investigated by DC leakage current measurement performed under varying humidity and potential bias conditions. Findings: The results show that the typical range of temperatures experienced by electronics during the wave soldering process is not sufficient for the removal of significant activator amounts. If the residues contain binary mixture of WOAs, the final ratio between the components, the residue level and the corrosive effects depend on the relative decomposition behavior of individual components. Among the WOA investigated under the conventional wave soldering temperature, the evaporation and removal of succinic acid is more dominant compared to adipic and glutaric acids. Practical implications: The findings are attributed to the chemistry of WOAs typically used as flux activators for wave soldering purposes. The results show the importance of controlling the WOA content and ratio between activating components in a flux formulation in relation to its tendencies for evaporation during soldering and the impact of its residues on electronics reliability. Originality/value: The results show that the significant levels of flux residues can only be removed at significantly higher temperatures and longer exposure times compared to the conventional temperature range used for the wave soldering process. The potential corrosion issues related to insufficient flux residues removal will be determined by the residue amount, its composition and ratio between organic components. The proper time of thermal treatment and careful choice of fluxing formulation could ensure more climatically reliable product.